2018
DOI: 10.1371/journal.pntd.0006470
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices (KAP) regarding leptospirosis among residents of riverside settlements of Santa Fe, Argentina

Abstract: BackgroundLeptospirosis is a global and re-emerging zoonotic disease caused by Leptospira spirochetes that are shed into the environment by infected animals. Humans can get infected via contact with animal hosts or contaminated environment. In Argentina, the highest annual incidences were reported in the province of Santa Fe, where epidemic outbreaks occurred during flooding events. This study examined the knowledge, attitudes and practices (KAP) regarding leptospirosis among residents of riverside slum settle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 39 publications
(58 reference statements)
7
47
0
Order By: Relevance
“…Interestingly, this finding was similar to several other studies conducted both in urban and rural settings. For urban setting, studies from Trinidad and Tobago [28], Puerto Rico [29], Jamaica [30], Argentina [31], India [32] and Malaysia [25, 26] showed similar results. Meanwhile, a recent study in rural setting in Malaysia discovered most respondents had poor knowledge level as well [33].…”
Section: Discussionmentioning
confidence: 87%
“…Interestingly, this finding was similar to several other studies conducted both in urban and rural settings. For urban setting, studies from Trinidad and Tobago [28], Puerto Rico [29], Jamaica [30], Argentina [31], India [32] and Malaysia [25, 26] showed similar results. Meanwhile, a recent study in rural setting in Malaysia discovered most respondents had poor knowledge level as well [33].…”
Section: Discussionmentioning
confidence: 87%
“…Several studies have shown that the KAP level in individuals is associated with effective prevention and management of illness and promotion of one’s own health [10] , [11] , [12] , [13] . On the contrary, deficiencies in KAP are linked to poor health and maladaptive disease preventive behavior [10] , [14] , [15] . Thus, it is expected that KAP levels of people with DM will be the deciding factor in their battle against COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…The "KAP theory" is a health behavior change theory wherein the change in human behavior includes three successive items, namely, gaining the right knowledge, generating of attitudes and adopting of practice (16). Many studies have illustrated that the KAP level in individuals is associated with effective prevention and management of illness and promotion of one's health (16,17,18,19) because de ciencies in KAP are associated with poor health and maladaptive disease preventive behavior, (17,20).…”
Section: Introductionmentioning
confidence: 99%